Analysis of The Implementation of Garage Ownership or Control Policy for Motor Vehicle Owners: A Case Study in The DKI Jakarta Province - Widya Prastika Retnaningtyas; Irfan Ridwan Maksum (Green Publisher Indonesia, 2024)
Traffic congestion is one of the problems faced by big cities in Indonesia, including DKI Jakarta Province. The increase in the number of motorized vehicles which is not balanced with the growth of roads and parking spaces causes traffic jams to get worse. The aim of this research is to examine the implementation of DKI Jakarta Provincial Regulation Number 5 of 2014 concerning Transportation regarding the obligation to own or control garages for motor vehicle owners. This research uses a qualitative approach with analytical descriptive research specifications. The data collection technique used is library research. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the implementation of DKI Jakarta Regional Regulation No. 5 of 2014 Article 140 involves a series of steps to ensure motor vehicle owners comply with the obligation to own or control a garage, including carrying out patrols and inspections in various areas of Jakarta to ensure vehicle owners comply with these rules, as well as the application of sanctions such as fines or other legal actions which can be an instrument. which is used to encourage vehicle owners to comply with regulations. However, there are several obstacles in implementing this policy, such as the limited number of garages available, expensive garage rental costs, and minimal supervision from the authorities.